Sustainable fashion for Aarong: the impact of fashion upcycling, chief branding officer & fashion e-commerce experience on the Bangladeshi consumers’ brand equity - Fahad, Shafayet Ullah (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.